Respon Akar Bibit Kelapa Sawit (Elaeis guineensis) Di Pre Nursery Pada Pemberian Naungan dan Abu Janjang Kelapa Sawit - Yetti Elidar (Agrifarm : Jurnal Ilmu Pertanian, 2017)
The aim of this research is to know the effect of shade and dosage of palm oil ash as well as their interaction to the root of oil palm plantation in pre nursery. This research was carried out in Nursery Faculty of Agriculture, Mulawarman University, Samarinda from February to May 2011. This research is an experiment arranged in Completely Random Design (RAL) with split plot analysis (4 x 4) with 5 replications. The main plot is the level of shade reduction (N) at the age of 10 weeks which consists of four levels, namely: no = Shade minus 100%, n1 = Shade minus 75%, n2 = Shade minus 50%, n3 = Shade minus 25%. As a plot child is a dose of ash (D) consisting of four levels: d1 = 11.5 g of ash / polybag equivalent to 23 tons / ha, d2 = 23 g of ash / polybag equivalent to 45 tons / ha, d3 = 34.5 g of ash / polybag equivalent to 68 tons / ha, d4 = 45 g of ash / polybag equivalent of 91 tons / ha. Data were analyzed statistically and tested further with the smallest real difference test (BNT) at 5% level. The results showed that the treatment of ash dose 23 g ash / polybag or equal to 45 ton / ha (d2) gave wet weight, dry weight, wet weight of leaf, average dry weight of leaves 5,51 g, 2,32 g , and 5.08 g. The shading treatment gives a mean wet weight of roots 1.90 g.